Our experience in treating Fournier’s gangrene at Max Hospital, Gurugram - Nigam, Vinod Kumar; Nigam, Siddharth (International Surgery Journal, 2021)
French venereologist Jean-Alfred Fournier described this gangrene as a fulminant gangrene of the penis and scrotum in young men. He reported five cases in his clinical lectures in 1883 though it was first described by Baurienne in 1764. Fournier’s gangrene is a form of necrotizing fasciitis that affects the genital and surrounding perineal and perianal areas. It’s a life-threatening disease leading to 20 to 80 percent mortality. It destroys tissues quickly and infection progresses to septic shock which kills patient if prompt and aggressive treatment is not started. Common symptoms of Fournier’s gangrene are pain in scrotum and or perineum, redness, fever and weakness. Advanced cases have foul smelling discharge from infected tissues. It is due to polymicrobial infection, both aerobic and anaerobic. Fournier’s gangrene is usually diagnosed clinically but imaging investigations such as X-rays, Ultrasound and CT scan help a lot to reach the diagnosis early. Treatment mainly consists of resuscitation, intravenous antibiotics and debridement. We have treated successfully four cases of advanced Fournier’s gangrene with team work of surgeons, anaesthesiologists, physicians and critical care specialists. Full recovery is possible due to a good team work and understanding the disease.